FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM (MPI) FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Djafar, Hamsiah (Idaarah: Jurnal Manajemen Pendidikan, 2017)
The presence of management education in the world of education has attracted many people’s attention to the world of education, as happened in the new academic year 2015 the number of applicants of students reaching the number of approximately 8000 an applicant candidate for new students in UIN ALAUDDIN Makassar as well as management enthusiasts the existing education at UIN Alauddin Makassar University experienced a significant increase of registrants especially in the Department of Management education. Although not all of the applicants can be admitted to the majors chosen by new students, this can not dampen the enthusiasm of new students to enter UIN Alauddin University’s lecture in Makassar especially in the Department of Education Management. Thus attract the attention of authors to study about Factors Affecting Students Choosing Islamic Education Management Study Program at the Faculty of Tarbiyah and Teacher UIN Alauddin Makassar Academic Year 2015/216. The factors that encourage students to choose to enter the Department of Islamic Education Management are due to their own desires, family support (older siblings, parents) and the Department of Islamic Education Management has been accredited B, as well as the time faculty in high school / equivalent.